2010
DOI: 10.1094/pdis-94-5-0528
|View full text |Cite
|
Sign up to set email alerts
|

Murraya paniculata and Related Species as Potential Hosts and Inoculum Reservoirs of ‘Candidatus Liberibacter asiaticus’, Causal Agent of Huanglongbing

Abstract: Huanglongbing (HLB), considered to be the most serious insect-vectored bacterial disease of citrus, is transmitted in nature by the Asian citrus psyllid Diaphorina citri and the African citrus psyllid Trioza erytreae. D. citri was discovered in southern Florida in 1998 and the HLB disease in 2005. Both have become established throughout citrus-producing areas of Florida. Murraya species are widely grown in southern Florida as ornamental hedges and are readily colonized by D. citri vectors. Colonies of D. citri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 9 publications
1
35
0
9
Order By: Relevance
“…L. asiaticus' cells/psyllid). In order to serve as an inoculum reservoir, a plant species should be able to retain the pathogen in an infectious state over an extended period of time (4). Our data showed that 'Ca.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…L. asiaticus' cells/psyllid). In order to serve as an inoculum reservoir, a plant species should be able to retain the pathogen in an infectious state over an extended period of time (4). Our data showed that 'Ca.…”
Section: Discussionmentioning
confidence: 84%
“…L. asiaticus'-infected S. buxifolia plants in pathways 2 and 3 were colonized by healthy psyilids. During the AAP, psyllids could mate and reproduce but only adults were used for inoculations (4,26). When new flushes were available on receptor plants for psyllid feeding, 10 psylhds from source plants were collected and transferred onto one receptor plant for at least 14 days of inoculation access period (IAP; 4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las has been reported to exist in a number of genetic groupings, depending on the DNA segment analysed [20] and the divergence on other DNA segments may be more useful for epidemiological purposes. Las is also known from close citrus relatives commonly grown for ornamental and culinary purposes, especially Murraya species [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Para as espécies que ocorrem no Brasil, Lopes et al (2009) (DAMSTEEGT et al, 2010). Gasparoto et al (2010) confirmaram a transmissão de Ca.…”
Section: Agentes Causaisunclassified